Outsourcing and Organisational Innovation: the Example of a Service Provider - Csaba Holyevácz (Theory, Methodology, Practice, 2013)
The history of the gas and oil industry in Hungary goes back to the mid-19th century. This industry and its participants have gone through an organisational structural transition that presents an exclusive example for establishing the modern corporate structure as well as ofvalue-creating opportunities in organisational development. In the present paper the notion of modern corporate organisation, the reasons for its establishment and its stages are presented through the example of a Hungarian gas provider, supported by theoretical outlooks. The organisational development of one of the largest Hungarian gas providers made since the market opening (2004) is an appropriate way of representing the economic and organisational benefit within the application of modern organisational theories and strategies. This development presents the effects of the implementation of modern efficiency measuring means and methods (Economic Value Added) in the management operation to meet the expectations of investors. Decisions and steps determining the changes in the corporate organisation give a good example of measures taken to improve the efficiency implemented by centralizing as well as by process optimizing restructurings according to LEANmanagement principles. The frequent presentation of decisions in classical (IT, mass data management) and competence-assessment-based outsourcing provides examples for effects of cost-saving opportunities and efficiency-improving measures. The main purpose of the paper is the presentation of organisational development based on the practical evidence of organisational theories and relationships through which theoretical conclusions are proved. In addition, the conception that the efficient practical application of relationships developed by theories means economic benefit for companies is also presented. However, development is still in progress. On the basis of the practical examples of the past and their theoretical connections there are further challenges in the networking of organisations and the virtual organisational structure.